Primary lung cancer metastatic to the breast: case report of a patient in remission - Pedro Marchiori Cacilhas; Kelly Mallmann Silva; Monique Wickert; Allan Arrieira Azambuja (Brazilian Journal of Oncology)
While lung carcinoma is the most common of the malignant tumors, primary lung tumors metastatic to the breast are rare and the prognosis is poor. We report a case of a Brazilian, 65- year-old, black, female patient with no family history of breast or lung cancer. During physical gynecological examination, she presented with a palpable nodule in the outer quadrant of the right breast. Based on X-ray, CT, PET-CT and immunohistochemistry investigation, a diagnosis of primary tumor metastatic lung to breast was made. The patient was referred for setorectomy and bi-lobectomy, combined with chemotherapy. She was in remission from November 2012 until December 2018. Given the poor prognosis related to the disease, the evolution presented is surprising.